As condições de vida dos assentados da região de Andradina: a realidade e os indicadores de avaliação da política pública de reforma agrária - Carvalho, Lívia Hernandes [UNESP] (2013)
The theme of this research is the rural settlements in the region of Andradina-SP, northwest of São Paulo, and it starts with the analysis of the history of the agrarian question in this region in order to contextualize the agrarian situation in the rural settlements surveyed. The objective was to analyze the public policy of agrarian reform in the region, focusing on indicators of quality of life improvement of the families settled. Questionnaires were administered to the heads of 244 families, which account for 10% of the sum of the families of the 30 settlements in the region of Andradina. The research was done through analysis of information of interest to this study, which involved quantitative data described and systematized using Microsoft Excel spreadsheet program for calculation of indicators and their averages. From this, the data were analyzed qualitatively in order to grasp its meaning from the broader reality that makes up the agrarian question and its uniqueness in the region of Andradina. The indicators were related to family composition, education, health, previous occupation, work, sources of income, social benefits, settlement infrastructure, community involvement and leisure. Based on the data, we found that there is an improvement in the living conditions of the settlers, however, the data collected show that the indicators used to evaluate public policy reform do not capture other elements that make up the reality agrarian, as the conditions of access to food, housing, education and other characteristics experienced in the settlements, just showing that monetary income is scarce and land reform policy deficit. Currently, land reform has been treated as social policy and not as a development policy